Asian consensus recommendations on optimizing the diagnosis and initiation of treatment of hepatitis B virus infection in resource‐limited settings. Issue 5 (23rd December 2019) - Gane, Edward John; Charlton, Michael R.; Mohamed, Rosmawati; Sollano, Jose Decena; Tun, Kyaw Soe; Pham, Thuy Thi Thu; Payawal, Diana Alcantara; Gani, Rino Alvani; Muljono, David Handojo; Acharya, Subrat Kumar; Zhuang, Hui; Shukla, Akash; et al.
Abstract: Asia has an intermediate‐to‐high prevalence of and high morbidity and mortality from hepatitis B virus (HBV) infection. Optimization of diagnosis and initiation of treatment is one of the crucial strategies for lowering disease burden in this region. Therefore, a panel of 24 experts from 10 Asian countries convened, and reviewed the literature, to develop consensus guidance on diagnosis and initiation of treatment of HBV infection in resource‐limited Asian settings. The panel proposed 11 recommendations related to diagnosis, pre‐treatment assessment, and indications of therapy of HBV infection, and management of HBV‐infected patients with co‐infections. In resource‐limited Asian settings, testing for hepatitis B surface antigen may be considered as the primary test for diagnosis of HBV infection. Pre‐treatment assessments should include tests for complete blood count, liver and renal function, hepatitis B e‐antigen (HBeAg), anti‐HBe, HBV DNA, co‐infection markers and assessment of severity of liver disease. Noninvasive tests such as AST‐to‐platelet ratio index, fibrosis score 4 or transient elastography may be used as alternatives to liver biopsy for assessing disease severity. Considering the high burden of HBV infection in Asia, the panel adopted an aggressive approach, and recommended initiation of antiviral therapy in all HBV‐infected, compensated or decompensated cirrhotic individuals with detectable HBV DNA levels, regardless of HBeAg status or alanine transaminase levels. The panel also developed a simple algorithm for guiding the initiation of treatment in noncirrhotic, HBV‐infected individuals. The recommendations proposed herein, may help guide clinicians, to optimize the diagnosis and improvise the treatment rates for HBV infection in Asia.